2014
DOI: 10.1038/ncomms4563
|View full text |Cite
|
Sign up to set email alerts
|

D-Glucosamine supplementation extends life span of nematodes and of ageing mice

Abstract: D-Glucosamine (GlcN) is a freely available and commonly used dietary supplement potentially promoting cartilage health in humans, which also acts as an inhibitor of glycolysis. Here we show that GlcN, independent of the hexosamine pathway, extends Caenorhabditis elegans life span by impairing glucose metabolism that activates AMP-activated protein kinase (AMPK/AAK-2) and increases mitochondrial biogenesis. Consistent with the concept of mitohormesis, GlcN promotes increased formation of mitochondrial reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(173 citation statements)
references
References 66 publications
(89 reference statements)
5
164
0
1
Order By: Relevance
“…In the study reported by Song et al (37), using a xenograft mouse lung tumor model, glucosamine was required to be introduced at a concentration as high as 500 mg/kg body weight in order to achieve a significant benefit of glucosamine. Furthermore, Weimer et al (38) reported that the plasma level of glucosamine in a mouse model may be increased up to ~2 µM. Notably, it was observed that the effects of glucosamine on ALDH + breast CSC viability are increased after 24 h of treatment, compared with after 48 h; however, the glucosamine treatments for longer durations were not performed in the present study due to MCF7 cells not surviving in serum-free treatment medium for ≥48 h. If the effect of stemness suppression is only short-term, it may indicate that glucosamine treatment should be repeated as necessary to replenish the effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the study reported by Song et al (37), using a xenograft mouse lung tumor model, glucosamine was required to be introduced at a concentration as high as 500 mg/kg body weight in order to achieve a significant benefit of glucosamine. Furthermore, Weimer et al (38) reported that the plasma level of glucosamine in a mouse model may be increased up to ~2 µM. Notably, it was observed that the effects of glucosamine on ALDH + breast CSC viability are increased after 24 h of treatment, compared with after 48 h; however, the glucosamine treatments for longer durations were not performed in the present study due to MCF7 cells not surviving in serum-free treatment medium for ≥48 h. If the effect of stemness suppression is only short-term, it may indicate that glucosamine treatment should be repeated as necessary to replenish the effect.…”
Section: Discussionmentioning
confidence: 99%
“…HP activation might lead to energy imbalance by consuming metabolites, triggering a stress response. This view receives support from the observation that glucosamine (GlcN) supplementation causes a ROS response [18 ] that extends worm and mouse lifespan through a hormetic mechanism.…”
Section: Current Opinion In Cell Biologymentioning
confidence: 98%
“…Low concentrations of paraquat, which is toxic at high concentrations, were reported to extend lifespan of C. elegans by generating ROS from mitochondria (Yang and Hekimi, 2010a). D-Glucosamine extends the lifespan of C. elegans by impairing glucose metabolism, and increases the mitochondria biogenesis that triggers mtROS generation (Weimer et al, 2014). The mood stabilizer lithium extends the lifespan of Drosophila through inhibition of GSK3 and activation of Nrf2 (also known as Cap-ncollar in flies) (Castillo-Quan et al, 2016).…”
Section: Pqq Is a Lifespan Extension Chemical With A Novel Action Mecmentioning
confidence: 99%
“…Various stimuli, such as mitochondrial dysfunction, calorie restriction, acute impairment of insulin signaling, glucose restriction or absence of a germline, can release mtROS to extend lifespan (Lee et al, 2010;Schaar et al, 2015;Schulz et al, 2007;Wei and Kenyon, 2016;Xie and Roy, 2012;Yang and Hekimi, 2010a,b;Zarse et al, 2012). The hypoxia inducible factor 1 (HIF-1), the stress-activated transcriptional factor SKN-1 (Nrf2 or NFE2L2 in mammals), AMP-activated protein kinase (AMPK) and molecules in the intrinsic apoptosis pathway including CED-4 (Apaf1 in mammals) also participate in mtROSmediated longevity signaling (Castillo-Quan et al, 2016;Hwang et al, 2014;Lee et al, 2010;Wei and Kenyon, 2016;Weimer et al, 2014;Xie and Roy, 2012;Yee et al, 2014;Zarse et al, 2012).…”
Section: Introductionmentioning
confidence: 99%